Assessing the influence of bibliometric factors and organizational characteristics on the centrality degree of inter-university collaborative networks: a neural network approach - Juan David Reyes-Gómez; Efrén Romero-Riaño (Information Research: An International Electronic Journal)
Introduction. The centrality degree of a university collaborative network indicates how many other universities the given university has active collaborations with. The study analyses the centrality of university-level collaboration networks and aim to assess the influence of organizational characteristics and bibliometric factors of universities on the centrality degree.